Rusty Brown - Ware, Chris 1967- (Pantheon Books, 2019)
"Rusty Brown" is a fully interactive, full-color articulation of the time-space interrelationships of six complete consciousnesses on a single midwestern American day and the tiny piece of human grit about which they involuntarily orbit. A sprawling, special snowflake accumulation of the biggest themes and the smallest moments of life, "Rusty Brown" literately and literally aims at nothing less than the coalescence of one half of all of existence into a single museum-quality picture story, expertly arranged to present the most convincingly ineffable and empathetic illusion of experience for both life-curious readers and traditional fans of standard reality. From childhood to old age, no frozen plotline is left unthawed in the entangled stories of a child who awakens without superpowers, a teen who matures into a paternal despot, a father who stores his emotional regrets on the surface of Mars and a late-middle-aged woman who seeks the love of only one other person on planet Earth
Keywords: Ware, Chris -- 1967-; Graphic Novel; Graphic novels; Comic